Phytochemical screening and determination of total phenolic and total flavonoid contents of pear peel extracts - Vinda Maharani Patricia; Fauzia Ningrum Saputri (Universitas Muhammadiyah Malang, 2019)
The study was carried out to investigate the presence of different phytochemicals as well as to determine the total phenolic and flavonoid contents of green pear/european pear peels and yellow pear/asian pear peels. Phytochemical screening of the pear peels was carried out following standard protocols. Total phenolic content was determined by Folin-Ciocalteu method and total flavonoid contents was determined by Aluminum Chloride Colorimetric method, measured using n-hexane, etil acetate, and methanol. Phenolics, flavonoids, tannins, alkaloids, and saponins are present in green pear and yellow pear peels. The total phenol and flavonoid contents are highest in methanol extracts in which green pear peels have a higher concentration than yellow pear peels. In conclusion, the green and yellow pear peels are rich in phenolic compounds and have great potential as natural antioxidants. Therefore, the results of this research should be considered to provide the possibility for future developments of highly functional antioxidants.